Geology for archaeologists : a short introduction - Allen, John R. L., (Archaeopress Publishing Ltd, 2017)
This short introduction provides archaeologists of all backgrounds with a grounding in the principles, materials, and methods of geology. Each chapter ends with a short reading list, and many have selected case-histories in illustration of the points made. Included is a glossary of technical terms.